Performance of groundnut (Arachis hypogaea L.) as influenced by phosphorus and zinc fertilization - Jeetarwal, R.L.; Jat, N.L.; Dhaka, M.S.; Jat, M.L.; Naga, Sunder Devi (Annals of Agricultural Research, 2016)
Performance of groundnut (Arachis hypogaea L.) as influenced byphosphorus and zinc fertilizationR.L. Jeetarwal*, N.L. Jat, M.S. Dhaka, M.L. Jat and Sunder Devi NagaDepartment of Agronomy, S.K.N. College of Agriculture, Jobner, Jaipur, Rajasthan-303 329E-mail: ratanjeetarwal@gmail.com